2012
DOI: 10.1002/cplu.201200233
|View full text |Cite
|
Sign up to set email alerts
|

Blue‐Emitting Nanocrystals, Microcrystals, and Highly Oriented Nanofibers Prepared by Reprecipitation and Solvent Drop‐Casting of 2‐Phenyl‐naphthoxazoles

Abstract: Three 2‐phenyl‐naphth[2,3‐d]oxazole derivatives, one of them being unsubstituted (1) and the two others bearing a methyl (2) and a tert‐butyl group (3) in the para position of the phenyl ring, were prepared. In the crystalline state, all compounds adopted a crossed‐stacking mode that favors fluorescence emission. They emitted in the blue region and their photoluminescence quantum yield ranged between 25 and 59 %. The preparation of micro/nanoparticles by simple methods was optimized. By using a solvent‐exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…The crystal unit cell contained two molecules. The PBO framework was planar, as already noticed for various derivatives of this compound and closely‐related 2‐phenylnaphthoxazole derivatives, and the dicyanovinyl group formed a small dihedral angle of around 11° with the rest of the molecule. Each molecule shared short contacts with six neighbours located on the same plane.…”
Section: Resultssupporting
confidence: 73%
“…The crystal unit cell contained two molecules. The PBO framework was planar, as already noticed for various derivatives of this compound and closely‐related 2‐phenylnaphthoxazole derivatives, and the dicyanovinyl group formed a small dihedral angle of around 11° with the rest of the molecule. Each molecule shared short contacts with six neighbours located on the same plane.…”
Section: Resultssupporting
confidence: 73%
“…The molar absorption coefficient (ε Abs ) is also an important parameter for the development of fluorescent probes. Samples prepared with naphth[1,2- d ]imidazoles IM1 – IM7 showed high ε Abs on the order of 10 3 to 10 4 M −1 cm −1 ( Table 1 ), which is consistent with the allowed transition π→π* of π-conjugated systems [ 26 , 28 , 29 , 30 ] characteristic of the imidazole nucleus [ 25 , 31 ].…”
Section: Resultssupporting
confidence: 60%
“…To increase the chances of developing highly fluorescent materials, a strategy is to work with the rare families of dyes that are not prone to plane-to-plane stacking. This is the case for the 4 0 -alkyl and 4 0 -alkoxy derivatives of 2-phenyl-benzoxazole [9] and naphthoxazole [10] that exhibit an original packing mode and display excellent fluorescence properties in the crystalline state. Our recent study revealed that small variations in the nature of the substituent borne by the phenyl ring lead to substantial changes in the spectroscopic and self-association properties.…”
Section: Introductionmentioning
confidence: 94%
“…The reprecipitation method is a mild method, based on solvent exchange. Primarily developed by Nakanishi and coworkers [39,40], it has proved to be very useful to us in preparing nano-and micro-crystals of various organic dyes [41e43], including benzoxazole and naphthoxazole dyes [9,10]. It generally consists in dissolving the organic compounds in a hydrophilic solvent, and then pouring a small volume of this concentrated solution into a large volume of water.…”
Section: Formation Of Microparticlesmentioning
confidence: 99%